Ethical Considerations in AI-Enhanced Strategic Management: Implications for Corporate Social Responsibility - Tovan; Mutmainah; Suwedy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the ethical implications of the application of artificial intelligence (AI) in corporate strategic management and its impact on corporate social responsibility (CSR). The method used is a systematic literature review with a qualitative approach, collecting secondary data from various relevant journals. The results of the analysis of 15 studies show various approaches in exploring the ethics and impact of technology, especially AI, on strategic management and CSR. Several studies highlight the challenges in creating inclusive ethical regulations through AI auditing and ethical standardization. Ethical concerns arise in the use of AI in sectors such as insurance, education, and retail, especially related to privacy protection and customer satisfaction. These findings emphasize the need for a strong ethical framework to ensure the fair and responsible use of AI.